Phytochemical Analysis of Eco-Enzymes Combining Coffee Husks and Cocoa Husks - Zuhrotul Mujayyanah; Melda Nurmaisari; Widia Rini Hartari; Supriyanto Supriyanto (G-Tech: Jurnal Teknologi Terapan, 2026)
Eco enzyme is a multipurpose fermentation liquid made from organic materials. The purpose of this study was to determine the qualitative phytochemical content in eco enzyme samples combining coffee husks and cocoa husks. The ratio used for the solid organic material:sugar:water was 3:1:10. The treatment focused on variations in water substitutes with solid organic materials in the form of coffee husks and cocoa husks, as well as molasses as a sugar substitute. There were four types of treatments, namely E1 (Control), E2 (Coconut Water), E3 (Coffee Pulping Water), and E4 (Rice Washing Water). The types of phytochemicals tested were phenols, alkaloids, flavonoids, tannins, saponins, and cardenolins. The test results were observed based on the color changes that occurred. The phytochemical content detected in the eco enzyme sample is phenols, alkaloids, flavonoids, tannins, and saponins, while the cardenoline content was detected negatively.